CREATIVE LEARNING METHODS TO INCREASE CLASS PARTICIPATION AND PROBLEM SOLVING SKILLS OF STUDENTS IN GLOBAL PERSPECTIVES SUBJECTS IN GRADE IX (NINE) SMP SPK SAMARINDA - Dewi Hanna Sri Wahyuli Siahaan; Saparso, Elika Dwi Muwarni, Sarah Prasasti (Adisam Publisher, 2024)
Schools play a crucial role in not only imparting knowledge but also in nurturing and enhancing students' abilities, equipping them to tackle the constant challenges they will encounter in various aspects of their lives. One way is to actively participate in class to improve problem solving skills. Based on the initial data collection carried out, it is known that Grade IX (Nine) students at SPK Samarinda Middle School exhibit a low level of problem-solving skills. The implementation of creative learning methods in Global Perspectives, a subject at SPK Samarinda Middle School, resulted in a remarkable increase in grade IX participation. The percentage rose from 49.76% to 76.68%, with a total of 26 students actively engaged.. Apart from that, teachers are also required to be creative teachers and can be facilitators with good planning, to be able to develop students' abilities, one of which is solving problems by considering various points of view and the impacts that will be affected. The creative learning methods used are: group activities, research, presentations, discussions and debates, were proven to be able to increase students' problem solving abilities from only 19.23% to 88.46%.